Pengembangan Sistem Monitoring Aset Berbasis Lokasi Pada Platform Mobile - Muchammad Rizal; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In an organization or company certainly has assets to support its operational activities, so it is very important to do the maintenance of the asset itself. Asset maintenance aims to track the status of the asset, including the location and condition of the asset. Maintenance of high-level assets with integrated systems is needed to increase effectiveness in carrying out asset maintenance. At the Faculty of Computer Science asset maintenance activities are carried out manually, namely by the staff tasked with examining assets directly, then the damaged assets are written in the book for later making reports manually. The manual bookkeeping causes data loss and poor data grouping. Location-based asset monitoring systems are designed and built to improve the effectiveness and efficiency of manual asset maintenance processes. This system is built on a mobile basis. This system uses location based service that will make it easier in the process of mapping the location of scattered assets and matching the location of monitoring and location of assets. Based on the results of usability testing shows that 89.8% of users agree that the system is worthy of being used and applied. Whereas in the functional and non-functional test results that this system is valid and feasible to use. This shows that this system has been successfully implemented in the asset maintenance section to produce applications that can be accepted by users, especially users in the Equipment Division of Faculty of Computer Science.